2018
DOI: 10.3389/fphar.2018.00033
|View full text |Cite
|
Sign up to set email alerts
|

Eriodictyol Attenuates Myocardial Ischemia-Reperfusion Injury through the Activation of JAK2

Abstract: Myocardial ischemia-reperfusion (I/R) injury remains the leading risk factor of disability and mortality worldwide. In this study, the myocardial protective effect of eriodictyol (EDT) and the underlying mechanism in an ex vivo model of global myocardial I/R was investigated. After treatment with different concentrations of EDT, the decreased hemodynamic parameters induced by myocardial I/R injury were significantly attenuated by EDT. The elevated levels of IL-6, CRP, IL-8, and TNF-α were effectively reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Eriodictyol is a natural flavonoid compound. Previous studies have shown that eriodictyol exerts anti-inflammatory and antioxidant effects both in vitro and in vivo (Li et al, 2018;He et al, 2019). However, the effects of eriodictyol on cancer and its underlying mechanisms largely remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Eriodictyol is a natural flavonoid compound. Previous studies have shown that eriodictyol exerts anti-inflammatory and antioxidant effects both in vitro and in vivo (Li et al, 2018;He et al, 2019). However, the effects of eriodictyol on cancer and its underlying mechanisms largely remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the essential role of oxidative stress and inflammatory responses in the pathogenesis of myocardial infarction [ 9 , 12 ], antioxidant stress and anti-inflammatory responses present novel strategies on harmful event prevention and myocardial dysfunction attenuation [ 14 , 15 ]. Therefore, the current study determined the effects of HXP treatment on serum levels of antioxidant enzyme SOD, the lipid peroxidation marker MDA, and proinflammatory cytokines (IL-6 and TNF- α ).…”
Section: Discussionmentioning
confidence: 99%
“…When inflammatory response occurs after myocardial infarction, inflammatory cytokines are released and the numbers of macrophages gradually increase, provoking further myocardial damage [ 13 ]. However, antioxidant stress response and anti-inflammatory may prevent these harmful events and attenuate myocardial dysfunctions [ 14 , 15 ]. In the pathophysiological processes of myocardial ischemia, heart injury can be aggravated due to the large number of inflammatory factors and oxygen free radicals [ 16 ], leading to critical syndromes such as arrhythmia and heart failure, and initiating the activation of many signaling pathways [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…JAK2 is a member of the JAK kinase family. Many studies have shown that JAK2 expression or functional changes are related to I-R injury in various organs such as myocardium [10], brain [11], and kidney [7]. MicroRNA (miRNA) is a class of single-stranded, noncoding RNA molecules made up of 22–25 nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that apigenin is closely related to JAK2-STAT3 pathway activity and ischemia-reperfusion injury [22]. The activity of the JAK2-STAT3 pathway is closely related to injury to the heart [8,10,12], kidneys [7,9], and brain [11]. Luo found that osthole reduced renal reperfusion injury by regulating JAK2-STAT3 pathway activity [7].…”
Section: Introductionmentioning
confidence: 99%